Actionable web analytics : using data to make smart business decisions - Burby, Jason; Atchison, Shane (Indianapolis, IN : Wiley publishing, 2007)
Provides information on developing a Web analytics strategy to help make strategic business decisions, plan a website, develop effective marketing, and create a culture of analysis within an organization.
Includes index.
Keywords: Web usage mining; Data mining; Internet users -- Statistics -- Data processing; Business enterprises -- Computer networks; Electronic commerce; Internet marketing; Web sites -- Design; Internet searching